Knowledge, attitudes and perceptions towards menopause among highly educated Asian women in their midlife. (December 2014) - Memon, Fouzia R; Jonker, Leon; Qazi, Roshan A
Objective: To determine knowledge levels, and attitudes and perceptions towards, menopause among highly educated Asian women in their midlife. Study design: A cross-sectional survey. Setting: Five teaching institutions in Hyderabad, Pakistan. Population: In total, 200 out of 225 (89% response rate) teachers, lecturers and professors, aged 40–59 years, were surveyed in 2013 using a self-administered questionnaire. Results: The mean age of responders was 48 years. Premenopausal and perimenopausal women attributed for 58%, whereas 42% were postmenopausal. All women had a masters degree; 15% had a PhD degree. Forty-six percent of responders thought they had sufficient knowledge about the menopause and 87% had positive perceptions about it, with 76% feeling life was easier and calmer as a result of it. Reported negative perceptions included 30% of women experiencing feelings of grumpiness, irritability, altered work capability and loss of femininity. Health professionals were an information resource. of 60% of cases, only 5% of participants knew about hormone replacement therapy and none knew about available alternative therapies. Conclusion: Despite the fact that the majority of women felt well informed and exhibited a positive attitude towards menopause, a strong urge for more knowledge was expressed. Public health care systems should mobilize resources and take measures to improve women's awareness and knowledge about menopause-related changes through a variety of educational tools and media, including the Internet. A recommendation would be for physicians to provide more information about menopausal symptoms and also therapies to alleviate these symptoms, regardless of the patient's socioeconomic background.